An intimate partner violence prevention intervention for men, women, and couples in Ethiopia: Additional findings on substance use and depressive symptoms from a cluster-randomized controlled trial - Leight, Jessica; Deyessa, Negussie; Verani, Fabio; Tewolde, Samuel; Sharma, Vandana (Public Library of Science, 2020)
Intimate partner violence (IPV) is linked to substance use by male perpetrators and is associated with an increased risk of depression for women who experience violence. Unite for a Better Life (UBL) is a gender-transformative intervention delivered to men, women, and couples in Ethiopia; previous evidence demonstrated the intervention significantly reduced experience of and perpetration of IPV when delivered to men and led to more equitable household task-sharing when delivered to men and couples. The aim of this analysis is to assess engagement in the UBL intervention and to examine the relationship between random assignment to the intervention and men’s past-year substance use and women’s reported depressive symptoms as measured at the individual level.